Silencing of STEAP3 suppresses cervical cancer cell proliferation and migration via JAK/STAT3 signaling pathway - Zouyu Zhao; Panpan Yu; Yan Wang; Hong Li; Hui Qiao; Chongfeng Sun; Lina Zhu; Ping Yang (Cancer & Metabolism)
Abstract Background Six-transmembrane epithelial antigen of prostate 3 (STEAP3), an essential constituent of the STEAP family protein, plays a notable role in promoting cancer proliferation and metastasis. Despite the importance of the STEAP gene family in tumor progression, the function of STEAP3 in cervical cancer (CC) remains unclear. Materials and methods The expression of STEAP3 protein in CC tissues and cell lines was identified using immunohistochemistry. The Reduced Representation Bisulfite Sequencing (RRBS) was used to detect global gene DNA methylation in CC tissues and paracancerous tissues. Cell viability, proliferation, migration, and invasion, were evaluated using the Cell Counting Kit-8 (CCK8), 5-ethynyl-2’-deoxyuridine (EdU), wound repair assay, and transwell assay, respectively. RNA sequencing was applied to explore STEAP3-related signaling pathways. Western blotting was performed to detect the expression of related proteins, including epithelial-mesenchymal transition (EMT) and Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling markers. Results Herein, STEAP3 was strongly expressed in CC tissues and associated with poor prognosis. CC samples exhibited lower levels of STEAP3 methylation than normal samples, and the methylation levels of CpG islands in STEAP3 were association with prognosis. In contrast to control group, STEAP3 knockdown suppressed the proliferation and invasion of CC cells and enhanced sensitivity to oxaliplatin. Silencing of STEAP3 led to reduced N-cadherin and vimentin levels and increased E-cadherin expression. RNA sequencing analysis suggested that STEAP3 mediated the activation of the JAK STAT3 signaling pathway. Additionally, inhibition of STEAP3 decreased the phosphorylation of JAK2 and STAT3. Interestingly, colivelin (a STAT3 activator) modified STEAP3-induced cell proliferation, invasion, and expression of related proteins in the EMT and JAK/STAT3 signaling pathway. Conclusion STEAP3 was significantly associated with CC progression mediated via the JAK/STAT3 signaling pathway and may serve as an effective therapeutic target.